The effect of inventory intensity, capital intensity, and leverage on tax avoidance - Yunira, Haervi; Lubis, Citra Windi; Lubis, Nurul Izzah; Khairunnisa, Khairunnisa (Enrichment : Journal of Management, 2025)
The objective of this research is to examine the impact of inventory intensity, capital intensity, and leverage Regarding tax avoidance among food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the period 2019–2023 period. The research adopts a quantitative method utilizing multiple linear regression analysis. The findings indicate that capital intensity Exhibits a positive and significant influence on tax avoidance, whereas inventory intensity and leverage do not Have a significant impact. At the same time. Concurrently, these variables are not found to significantly influence tax avoidance.